Conflict Management among Students as a Strategy to Build Child Friendly Schools - Sapitri, Wina; Haprilwanti, Nenden; Sam'un, Sam'un; Baihaqi, Mohammad Aqil; Erihadiana, Mohamad (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Conflict between students is an unavoidable dynamic in the school environment, especially at the primary and secondary education levels. If not managed properly, these conflicts can have a negative impact on students' social-emotional development and disrupt the creation of a conducive learning atmosphere. This study is motivated by the importance of conflict management as part of strategic efforts in creating child-friendly schools. The purpose of this study is to analyze the forms of conflict between students, evaluate the conflict management strategies used by the school, and assess the effectiveness of the approach in creating a safe, inclusive and comfortable educational environment for all learners. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation in one of the public elementary schools that implement a child-friendly school program. The results showed that conflicts that often occur are related to differences of opinion, academic competition, and social dynamics. Conflict management strategies implemented include mediation by teachers, student discussion forums, and habituation of tolerance and empathy values. The conclusion of this study states that conflict management based on a humanist and participatory approach is proven to be able to reduce the intensity of conflict and strengthen social relations between students.